Community Education and Training on Biochar Production for Climate Change Mitigation and Adaptation in Arabica Coffee Cultivation - Anis Nugrahawati; Syahirman Hakim; Rossy Azhar; Dani Pratama Putra; Salman Salman (ABDISAINS, 2026)
This community service activity aims to improve the knowledge and skills of coffee farmers in utilizing biomass waste into biochar as an effort to mitigate and adapt to climate change. The activity was carried out at the Mekar Ayu Farmers Group, one of the Arabica coffee producing farmer groups in Central Aceh Regency with 25 members. The implementation method included socialization about the concept and benefits of biochar for soil and plants, training in making biochar using agricultural waste materials (coffee skins and sawdust), and mentoring in applying biochar to coffee fields. The results of the activity showed that participants understood the function of biochar in increasing soil fertility, improving soil structure, and increasing water absorption efficiency. In addition, farmers were able to produce biochar independently using simple, environmentally friendly technology. This activity contributed to increasing the capacity of farmers in dealing with the impacts of climate change and supporting sustainable coffee farming. Keywords: Biochar, Climate Change, Arabica Coffee, Farmer Empowerment